Optimal memory time Cache partitioning in chip-multiprocessors - Hao LI; Lun-guo XIE (Tongxin xuebao)
Optimal memory time Cache partitioning(OMTP) was proposed.The OMTP can get the average access invalidation overheads of different application and Cache line distributation about Cache hit through the characteristic obtain unit.According to which the OMTP can allocate proper Cache capacity to competitive process,so the overall performance of the program can achieve optimizied.The experiment results showed that OMTP had higher miss rate compared with utility-based Cache partitioning(UCP),but it had better IPC throughput and weighted speedup,OMTP improved throughput by average 3.1% and weighted speedup by average 1.3% over UCP.